2007
DOI: 10.1177/0002764206297580
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining the Longer Term Stability of the Scientist-Practitioner Model of Training

Abstract: This study adds to the growing body of research on scientist and practitioner interests by empirically examining temporal stability as a function of experiences gained through the successful completion of a doctoral-level scientist-practitioner model-based training program in school or counseling psychology. Twenty-six participants, who completed the paper-and-pencil version of the Scientist Practitioner Inventory between 1996 and 2002 at the beginning of their doctoral program, recently completed an online ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Students at Social Psychology show relatively more interest in foreign languages and cultural topics. The picture emerging from group differences in personality and cognitive abilities is consistent with previous findings in the US (Bishop & Bieschke, 1998;Horn et al, 2007;Leong et al, 2007;Mallinckrodt et al, 1990;Martin et al, 2007;Tinsley et al, 1993;Vittengl et al, 2004). The different specialties of psychology can best be characterized in terms of different Holland codes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Students at Social Psychology show relatively more interest in foreign languages and cultural topics. The picture emerging from group differences in personality and cognitive abilities is consistent with previous findings in the US (Bishop & Bieschke, 1998;Horn et al, 2007;Leong et al, 2007;Mallinckrodt et al, 1990;Martin et al, 2007;Tinsley et al, 1993;Vittengl et al, 2004). The different specialties of psychology can best be characterized in terms of different Holland codes.…”
Section: Discussionsupporting
confidence: 85%
“…On the basis of nine interest scales, approximately 50% of the students were assigned to the correct specialty, even after cross-validation. Our results suggest that these interests are relatively stable (Horn et al, 2007;Zachar & Leong, 2000) and may have already crystallized quite early in the study.…”
Section: Discussionmentioning
confidence: 65%
“…As early as 1949, doctoral training standards for 'scientist-practitioners' were suggested in an attempt to integrate psychological research and practice (Baker and Benjamin, 2000;Horn et al, 2007). As the concept of the scientist-practitioner developed, an 'attitude of science' was promoted that encouraged 'skepticism, curiosity and inquiry', combined with the art of clinical practice (Striker, 2000, p. 254).…”
Section: Clinical Approachesmentioning
confidence: 99%
“…Also, as expected, interests in the fields of enterprising appeared linked to the I-O psychology area, reinforcing interest in business activities. The absence of social interest in the fields of I-O psychology can be explained by the greater focus on the abstract, personal achievement, as well as on a lower propensity to help people (Horn et al, 2007). The area of artistic interest was positively correlated with the I-O dimension, and negatively correlated with educational interests.…”
Section: Discussionmentioning
confidence: 97%
“…This is reflected clearly in the interests of the students who choose these specialties. Empirical evidence has shown that students in clinical psychology have higher scores with regards to helping people, whereas students in psychological methods have higher scores in the abstract and technical domain (Horn et al, 2007). Lastly, results from the Dutch ''StudieKeuze-InteresseTest'' (SKIT-6;Vorst, 2002) revealed that students of psychonomics presented a higher preference for logical and abstract reasoning and reveal lower scores with regards to helping people (Horn et al, 2007;Wicherts & Vorst, 2010).…”
Section: Interests In Career Areas Of Psychologymentioning
confidence: 99%